Seed Yield and Quality of Okra as Influenced by Sowing Time and Plant Spacing under Farmer’s Situation in Northwest Bangladesh - M.M. UDDIN; M.F. MONDAL; S. SAMSUZZAMAN; M.A. SIDDIQUE (Seed Research, 2026)
An experiment was conducted in the farmers’ field at Ghagot Para, Rangpur Sadar, Bangladesh during February to October 2003 as a collaborative programme of BARI and RDRS to observe the influence of sowing time and plant spacing on the growth, seed yield and quality of okra. Five sowing times, starting from February to June (15th of each month) and three different plant spacing (60 cm x 30 cm, 60 cm x 40 cm and 60 cm x 50 cm) were used as treatment variables. The highest seed yield was recorded from April sowing (1514.88 kg/ha) and the quality seed was also produced from the same sowing time (84.56% germination and 27.02 seed vigour index). The plants spaced at 60 cm x 40 cm produced the highest seed yield (1043.96 kg/ha) compared to other two tested spacings, but the best quality seed (74.00% germination and 23.79 seed vigour index) was obtained from the wider spacing (60 cm x 50 cm). Regarding combined effect, the highest seed yield was obtained from April sowing with 60 cm x 40 cm plant spacing (1609.63 kg/ha) and that of the lowest from February sowing with 60 cm x 30 cm plant spacing (325.37 kg/ha).